Clinicopathological study and management of liver abscess in a tertiary care center - Ratnottar, Jigar; Chauhan, Harish; Modh, Foram (International Surgery Journal, 2019)
Background: Liver abscess is a burning problem in tropical nations, with often lethal consequences and diagnostic/therapeutic challenges. We have determined etiopathology, clinical, radiological, and bacteriological characteristics of this condition and review its management strategies. Methods: During the period of the month from August 2017 to August 2018, a prospective study was performed involving 125 patients admitted to the in-patient ward of the Department of General Surgery of SMIMER Medical College their diagnosis was made on the basis of clinical features (such as right upper abdomen pain, and fever), laboratory investigations and radiological evidence of liver abscess. Results: Amoebic liver abscess was the most common (88%) type of liver abscess among the study groups. There was a strong correlation with the occurrence of liver abscesses and addiction to alcohol, history of diabetes mellitus and low socioeconomic status. The most common etiology of pyogenic liver abscess was Escherichia coli. Ultrasonography (USG) of the abdomen was accurate and cost-effective in diagnosis of liver abscesses. Percutaneous catheter drainage was the most effective method of treatment (with a 100% success rate). Conclusions: Most patients in our study had liver abscess of amoebic origin and had temporal relationship with diabetes, alcoholism, and staggering socioeconomic status. We suggest early recognition of clinical features and prompt abdominal USG as cost-effective means for treatment initiation and reducing complications.